Factors Affecting Cashew Nut (Anacardium occidentale L.) Production in Lamorende Village, Tongkuno District, Muna Regency - Hidayah, Wa Ode Arsy; Yunus, Lukman; Rosmawaty (International journal of technology and education research, 2025)
This study aims to: (1) determine the factors that influence cashew production in Lamorende Village, Tongkuno District, Muna Regency, (2) determine the production elasticity of each input on cashew production in Lamorende Village, Tongkuno District, Muna Regency. The types and sources of data in this study use primary data and secondary data with data collection techniques through observation, interviews, and literature studies. The data analysis used is the Cobb-Douglas analysis, which is transformed into a linear form by applying the natural logarithm (ln). The results of the analysis show that of the four input variables studied, namely land area, number of trees, labor, and plant age, only two variables have a significant effect on cashew production, namely land area and number of trees. These two variables have a positive and real effect on increasing cashew production, while labor and plant age do not have a significant effect on production. The results of the production elasticity analysis show that the variable number of trees has an elasticity value of more than one (elastic), while land area, labor, and plant age have an elasticity value of less than one (inelastic). This indicates that increasing the number of trees has a greater impact on production than other variables. Furthermore, the returns to scale (RTS) of cashew farming in Lamorende Village are in a state of increasing returns to scale, with a total elasticity value of 1.467